Process simulation and performance optimization for the oxidation ditch sewage treatment plant in Baguio City through the application of IAWQ activated sludge model - Dulay, Josephine Aries L. (2002)
The organic and nitrogen impurities removal of the oxidation ditch of Baguio City Sewage Treatment Plant was investigated through the application of the Activated Sludge Model No. 1 in the Activated Sludge Simulation Program. Detailed wastewater characterization is necessary to produce accurate estimates of process performance. The ASM authors recommended the methods used in the characterization of wastewater. The inert particulate organic matter, Xi, inert soluble organic matter Si, readily biodegradable substrate Ss, Slowly biodegradable substrate Xs, and heterotrophic biomass Xh, were determined experimentally with values 12.01 to 13.05% Xi, 10.20% Si, 24.24% Ss, 43.06 to 44.10% Xs and 9.45% Xh. The wastewater component fractions of Baguio Citiy where within range estimated by the Inhternational Association of Water Quality (IAWQ) used in ASM 1 with values 15% Xi, 10% Si, 25% Ss, and 45% Xs. A few of the stoichiometric and kinetic coefficients were experimentally determined. These were the heterotrphic yield, Yh, maximum specific grownth rate of heterotrophs u^h and and heterotrophic decay coefficient bh with values of 0.638874,8.94 and 0.447 respectively. Likewise, the ASM authors recommended the methods used in the parameter determination.